Empowering Rural Housewives Through Creative Packaging Design: The Case of Beneng Taro Products in Juhut Village, Banten - Agustina, Sri; Ummi, Nurul; Rahman, Arief; Pramudita, Marta; Al Aziz, Muhammad Daffa; Priyatna, Aufa Irsyad (SPEKTA (Jurnal Pengabdian Kepada Masyarakat : Teknologi dan Aplikasi), 2025)
Background: This community service program was conducted in Juhut Village, Pandeglang, Banten, to address limited market access of Beneng taro-based food products produced by local housewives. Despite abundant raw materials, product competitiveness remains low due to unsafe processing practices and poor packaging design. Contribution: This program bridges the gap between product quality and consumer trust by integrating food safety education with creative packaging innovation. It offers a participatory model that strengthens visual identity, labeling compliance, and branding for rural microenterprises. Method: The program applied a participatory approach involving 20 local women from the Sendaloka group. Activities included technical training on oxalate reduction techniques, visual communication in packaging, and safe food processing. Results: The initiative led to the development of Talaschips, a branded Beneng taro chip product with complete labelling, health claims, and consumer-oriented design. Evaluation showed a 65% increase in knowledge based on post-training interviews, and more than 30% of participants expressed intent to register their products for food certification. Conclusion: The program effectively empowered rural women by improving their technical and design capabilities. It fostered self-recognition as legitimate entrepreneurs and improved market access for local food products. The model is scalable and can be adapted to other rural settings for inclusive economic development and gender-equitable entrepreneurship.